The Role of Parents in Supporting Early Childhood Social Development in the Digital Age: A Systematice Literature Review - Eneng Sunengsih; Noviana Mustapa; Siti Aisyah; Mukti Amini; Ika Budi Maryatun (Murhum : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to systematically synthesize current evidence on the role of parents in supporting early childhood social development in the digital era and to identify an integrated framework for effective digital parenting. A Systematic Literature Review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were collected from Scopus, EBSCO, and Open Knowledge Maps using the keywords parental role, social development, early childhood, and digital era. After applying predefined inclusion and exclusion criteria, 25 peer-reviewed articles published between 2019 and 2024 were selected and analyzed using thematic content analysis. The findings indicate that effective parental involvement extends beyond screen-time regulation to encompass three complementary roles: supervisors, companions, and mentors. Parents who actively monitor technology use, engage in shared digital and offline activities, and provide guidance on responsible digital behavior are more likely to foster children's social competence while minimizing the risks associated with excessive technology use. The novelty of this study lies in proposing an integrated conceptual framework that synthesizes fragmented evidence into these three interconnected parental roles, providing a more comprehensive understanding of digital parenting than previous studies.